Implementation Of The Zone Of Proximal Development (ZPD) In Vygotsky's Theory - Andhiara Navira Recha; Nurul Hidayati (Indonesian Journal of Educational Technology, 2026)
Lev Vygotsky's sociocultural theory, particularly the Zone of Proximal Development (ZPD), remains a foundational lens for designing learning that is challenging, dialogic, and responsive to learner diversity. However, ZPD is often reduced to a simple gap between what students can and cannot do, whereas its educational value lies in the dynamic relation among learners, more capable others, cultural tools, tasks, and gradually changing forms of assistance. This article aims to strengthen the conceptual and practical discussion of ZPD implementation through a narrative literature review. Twenty relevant references on sociocultural theory, scaffolding, classroom interaction, learning technology, and qualitative analysis were examined and synthesized thematically. The review shows that effective ZPD-based instruction requires four integrated processes: diagnosing students' actual development, designing tasks slightly beyond independent performance, providing contingent scaffolding through modeling, questioning, feedback, tools, and peer collaboration, and gradually fading support while transferring responsibility to learners. The discussion also highlights potential risks, including over-scaffolding, superficial peer tutoring, time constraints, and inadequate teacher preparation. The article concludes that ZPD and scaffolding are not merely techniques but a pedagogical framework for adaptive learning. Their successful implementation depends on teachers' ability to read students' emerging understanding, orchestrate meaningful social interaction, and use technological resources as flexible supports rather than substitutes for pedagogical judgment.